Simulation Study of Natural Ventilation in Traditional and Contemporary Javanese Houses in Yogyakarta - Tri Yuni Iswati (RUAS (Review of Urbanism and Architectural Studies), 2011)
Background research is to see how many contemporary houses that much different from the Javanese house, contemporary house is usually attached to each other neighbor's house, do not have a yard, use half a stone wall, while the Javanese house has a large yard, far enough distance between the house and use a single wall stone. Objectives of this paper is to show natural differences in ventilation resulting from the use of materials, and types of homes are these different settings. Methodology used is to use CFD simulations to see how the difference and temperature difference. Using the measurement data base BMKG with winds measured at a height of 10m on the hottest and coldest months. Outcomes are the temperature and wind speed in Java proved to be more comfortable home. Summary The results proved that the traditional Javanese house more comfortable because it uses the hinge side windows, that make it easier for air to flow than the type of window (upper hinge) and one brick wall material further inhibit heat conduction than half brick wall.Keywords: natural ventilation, traditional house, contemporary house